A DESCRIPTIVE STUDY ON TEACHING SPEAKING OF REPORT TEXT BASED ON SCHOOL LEVEL-BASED CURRICULUM AT THE NINTH YEAR OF SMP N 1 KARTASURA IN 2010/2011 ACADEMIC YEAR - SUMIHADININGRUM, ARSI (2011)
In this study, the writer describes the implementation of teaching speaking of report text and the problem faced by the teacher in teaching speaking of report text based on school-based curriculum at the ninth year of SMP N 1 Kartasura. The writer uses descriptive qualitative research, which does not use statistic data. The writer did interview with the English teacher and the students of IX C class, and observed the process of speaking teaching-learning at the ninth year of SMP N 1 Kartasura. Based on the data analysis, it can be concluded that the objective of teaching speaking of report text based on School-based Curriculum at the ninth year in SMP N 1 Kartasura is to develop the students courage to speak English in front of the audience, and make the students understand report text in English speaking. The syllabus of English lesson in SMP N 1 Kartasura is a plan arranged by the teacher. The type of syllabus is product-oriented syllabus. In the teaching, the teacher does not only use text book as the source of the material but also uses a worksheet to make the students understand the material more. In conducting the teaching-learning process of teaching English, especially on teaching speaking of report text, the teacher used four procedures, namely: Building Knowledge of the Field (BKOF), Modeling of Text (MOT), Join Construction of Text (JCOT), and Individual Construction of Text (ICOT). The techniques implemented by the teacher in teaching speaking of report text are group discussion and questionanswer. By using those variations of the technique, the students do not feel bored and more enjoyable in receiving the materials. The writer finds the problem faced by the teacher, they are classroom condition, classroom management, less facilities, and limited time.